Cervical ripening and induction of labor in postdate pregnancy by Foley catheter insertion into the cervix as outpatient and inpatient - Masoumeh Mirteimori; Farideh Akhlaghi; Seyedeh Azam Pourhoseini (Mashhad University of Medical Sciences, 2021)
Introduction: One of the most common methods of pregnancy termination in postdate pregnancies is cervical ripening by insertion of a Foley catheter in the hospital. Recently, some studies have been performed on cervical ripening as outpatient to reduce the length of hospital stay. This study was performed with aim to compare the results of outpatient and inpatient cervical ripening. Methods: This case-control study was performed on 231 women with prolonged pregnancies in 2019. First, Foley catheter was inserted through the cervix. Outpatient group was sent to the home and the other group was hospitalized. After spontaneous excretion of the catheter, induction was performed in both groups using misoprostol and oxytocin. Duration of catheter insertion until its excretion and until delivery, dose of misoprostol and oxytocin, length of hospital stay, incidence of postpartum fever and rate of cesarean section were determined in both groups. Data were analyzed by SPSS software version 16) and Chi-square, independent T-test and or non-parametric equivalent tests. p < 0.05 was considered statistically significant. Results: The time interval between Foley catheter incretion and excretion (P=0.000) and the time interval between insertion of the Foley catheter and delivery (p=0.046) was significant between the two groups and was less in the hospitalized group. The need for misoprostol (p=0.001) and oxytocin (p=0.02) was different between the two groups and was less in the outpatient group. Mode of delivery (p= 0.892) and postpartum fever (p=0.202) was not significantly different between the two groups; the duration of hospitalization was shorter in outpatient group (p=0.051). Conclusion: Outpatient cervical ripening in postdate pregnancy has no complication and shortens the duration of hospitalization.